Aroma-active compounds in Russian sturgeon (Acipenser gueldenstaedtii) raised in recirculating aquaculture systems - Rodrigues da Silva, Mariana; Egiddi, Matteo; Debeuf, Bastien; Büttner, Andrea; Loos, Helene (Journal of Agriculture and Food Research, 2024)
The rearing system affects the nutritional and sensorial qualities of the Russian sturgeon (Acipenser gueldenstaedtii), a niche yet commercially valuable aquaculture species for caviar production. In the present work, we aimed to comprehensively characterize the odorant composition of fillets from Russian sturgeon raised in a recirculating aquaculture system (RAS) and discuss potential sources and formation pathways. A total of 114 odorants were detected through the application of combined sensory-instrumental analyses, of which 88 were successfully identified and 20 substances were found to be among the most potent odor constituents. The most dominant odorants were assigned to several specific substance classes, including aldehydes, alcohols, terpenes, ketones, organic acids, lactones, heterocycles, aromatic hydrocarbons, and sulfur-containing aldehydes. The compounds (E)-hex-2-enal, (Z)-hept-4-enal, cuminaldehyde, non-3-yn-1-ol, 3-carene, 2-methylisoborneol, geosmin, oct-1-en-3-one, nonan-3-one, (Z)-1,5-octadien-3-one, octane-2,3-dione, nonan-2-one, hexanoic acid, γ-crotonolactone, γ-octalactone, 2-acetyl-thiazoline, methional, and (2E,4Z,7Z)-trideca-2,4,7-trienal had high flavor dilution factors and are described for the first time as potent odor-active compounds associated with the Russian sturgeon. Overall, oct-1-en-3-one, (Z)-1,5-octadien-3-one, octane-2,3-dione, nonan-2-one, 2-methylisoborneol, and hexanoic acid had the highest flavor dilution factors. This study offers a basis for future development in the sturgeon RAS industry from the perspective of flavor characterization by providing deep insights into the fundamental composition and origins of the complex world of aquaculture fish aroma.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Aroma extract dilution analysis; Gas chromatography–mass spectrometry; Identification; Smell; Solvent-assisted flavor evaporation; Two-dimensional gas chromatography with mass spectrometry and olfactometry

Identification of odor-active compounds in Nile tilapia (Oreochromis niloticus) from recirculated aquaculture systems: A case study with different depuration procedures - Rodrigues da Silva, Mariana; Loos, Helene; Büttner, Andrea (Food Research International, 2024)
Off-flavors are a major challenge for companies using recirculated aquaculture systems (RAS). In the presented work, we comprehensively characterize the odorant composition of Nile tilapia (Oreochromis niloticus) raised in RAS and compare the impact of two depuration processes on the odorant composition and aroma profile of the fish. Fish collected from the production tank and after two different tank pre-disinfection approaches in the depuration process (high pH versus H2O2) were investigated. A combined sensory-instrumental investigation revealed the presence of 115 odorants, of which 83 were successfully identified. The compounds decanal, tridecanal, (Z)-1,5-octadien-3-one, octane-2,3-dione, benzophenone, non-3-yn-1-ol, γ-dodecalactone, (Z)-geranylacetone, 2,3-diethyl-5-methylpyrazine, 1-methylpyrrolidin-2-one, 2-acetyl-2-thiazoline, benzothiazole, skatole, and 5α-androst-16-en-3-one were detected with the highest flavor dilution factors and are described for the first time as odor-active compounds in fish from RAS. The results indicate that depuration decreased the levels of 78 different odorants from the fish, including the potent earthy smelling odorants geosmin, isoborneol and 2,3-diethyl-5-methylpyrazine.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Aroma extract dilution analysis; Gas chromatography-mass spectrometry; Gas chromatography–olfactometry; Smell; Solvent-assisted flavor evaporation; Two-dimensional gas chromatography with mass spectrometry and olfactometry

More than just geosmin and 2-methylisoborneol? Off-flavours associated with recirculating aquaculture systems - Noguera, Pedro Martínez; Egiddi, Matteo; Södergren, Julia; Rodrigues da Silva, Mariana; Beauchamp, Jonathan; Petersen, Mikael Agerlin; Büttner, Andrea; Jørgensen, Niels O.G. (Reviews in Aquaculture, 2024)
The consumption of seafood is driven by flavour, yet achieving its high quality remains a challenge for many species reared in recirculating aquaculture systems (RAS). A comprehensive knowledge of off-odour sources in aquatic foods is indispensable in ensuring flavour quality standards. At the beginning of the production chain, early post-harvest lipid oxidation products develop into endogenous off-odours and accumulate over time. These malodours add to those already absorbed exogenously, namely from the water and feeds, although the information on the interactions between these sources is currently scarce. Despite geosmin and 2-methylisoborneol receiving significant attention in relation to fish off-flavour, only limited knowledge on the molecular and ecological mechanisms driving their production in aquatic environments has been reported. Moreover, RAS-hosted bacteria have been associated with a wide range of other odour-active compounds, such as pyrazines, terpenoids, and other degradation byproducts that are frequently overlooked when studying flavour taint in fish. The influence of aquaculture feeds on the flavour of fish flesh has been underestimated, too, both as a source of off-odours but also as a novel modulator strategy to achieve desirable aquatic food flavours. Finally, the influence of water treatment processes widely used in RAS operations, such as advance oxidation process, ozone, ultraviolet and hydrogen peroxide disinfections, is greatly underexplored with respect to odour quality. This article reviews the current scientific evidence with supporting data on the chemical diversity of off-odours found in aquaculture fish worldwide and their potential sources and highlights knowledge gaps that should be addressed in future research.
CRIS-Team Scopus Importer:2024-07-12
Keywords: endogenous; feed-borne; microbial; off-odour; RAS; waterborne